Are Cesarean Section and Appendectomy in Pregnancy and Puerperium Interrelated? A Cohort Study - Şahin, Banuhan; Tinelli, Andrea; Augustin, Goran (Frontiers in Surgery, 2022)
Introduction: It is not known whether appendectomy for acute appendicitis (AA) increases the Cesarean section (CS) rate and whether CS increases the likelihood of AA and appendectomy in the early puerperium. In this study, delivery type and delivery outcomes and appendectomy during pregnancy and puerperium were analyzed. Methods: This cross-sectional retrospective study was performed on 11513 women, delivered during 2015-2020. Inclusion criteria were patients submitted to appendectomy for AA during pregnancy and the first six weeks after delivery. Evaluating parameters were age, parity, gestational week at birth, delivery type, and babies' birth weight. Results: Thirty-two patients underwent appendectomy: 12 during pregnancy (2 in the first trimester, 6 in the second trimester, 4 in the third trimester) and 20 women during puerperium. 58.2% of pregnant women and 65% of puerperal women were submitted to CS. Discussion: Half of the women who underwent appendectomy for AA during pregnancy may require urgent CS. The cause of acute abdomen in the postpartum period, especially in the first week, could be AA, especially in women delivered by CS.